Projections of climate change‐driven variations in the offshore wave climate off south eastern Australia. (9th July 2012) - Hemer, M. A.; McInnes, K. L.; Ranasinghe, R.
ABSTRACT This study presents an analysis of the wind‐wave climate on the south‐east Australian continental margin and its potential changes under the effects of projected climate change. The wind‐wave climate is modelled for three 20 year time‐slices (1981–2000, 2031–2051, and 2081–2100) using a dynamical wave modelling approach in which the WaveWatch III spectral wave model, with a nested domain SWAN model, is the region of interest. Surface wind forcing is obtained from an ensemble of three global climate model runs (CSIRO Mk3.5, GFDLcm2.0, and GFDLcm2.1) dynamically downscaled using CSIRO's Cubic conformal atmospheric model (CCAM), under two greenhouse gas emission scenarios (a high emission SRES A2 and low emission SRES B1 scenario). A third level of uncertainty associated with adjusting climate model derived winds for climate and variability bias is found to be the largest source of uncertainty among the limited range of sources considered in the twenty‐eight 20 year wave model simulations undertaken herein. The ensemble of wave model runs for the 2081–2100 time‐slice project a robust decrease in mean significant wave height along the south‐east Australian coast relative to present (1981–2000) conditions. The magnitude of projected change in mean annual significant wave height is less than 0.2 m, with larger values in the north of the region of interest, and is associated with a projected decrease in storm wave energy in the region. An anticlockwise rotation in mean wave direction of approximately 5° is also projected over the same period. Copyright © 2012 Royal Meteorological Society